2022
DOI: 10.1111/jfbc.14128
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and NF‐κB inactivation implicate glycyrrhizic acid‐induced G 1 phase arrest in hepatocellular carcinoma cells

Abstract: Tang were the most common herbal medicine prescriptions for significantly reducing overall mortality in patients with liver cancer (Liao et al., 2015). Herbal medicine has been shown as adjunctive therapy to effectively improve quality of life and prolong overall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Then, the PEI would reach the nuclear membrane without accumulation inside the nuclei where it creates local holes either by tiny disruption of the membrane or by PEI-supported holes . Through these holes, the PEI delivers its cargo and, in this study, it delivered the DOX to the nuclei. Consequently, the results revealed a cellular-enhanced active targeting of the HCC cells through the GA–GA receptor binding and subcellular (nuclear) targeting by the PEI-based shell to deliver the DOX to the nucleus.…”
Section: Resultsmentioning
confidence: 86%
“…Then, the PEI would reach the nuclear membrane without accumulation inside the nuclei where it creates local holes either by tiny disruption of the membrane or by PEI-supported holes . Through these holes, the PEI delivers its cargo and, in this study, it delivered the DOX to the nuclei. Consequently, the results revealed a cellular-enhanced active targeting of the HCC cells through the GA–GA receptor binding and subcellular (nuclear) targeting by the PEI-based shell to deliver the DOX to the nucleus.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, the expression level of intracellular γH2AX protein comes off as strong evidence of DNA damage in cells and is widely used in cancer research. Wang et al (2022) proposed that GA could inhibit DNA damage repair and induce apoptosis. The outcomes of this research suggested that the triggering mechanism of GA apoptosis may be achieved by inhibiting DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. (2022) proposed that GA could inhibit DNA damage repair and induce apoptosis. The outcomes of this research suggested that the triggering mechanism of GA apoptosis may be achieved by inhibiting DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and 1% penicillinstreptomycin (PS). Following this, the cells underwent incubation in a controlled environment, maintained at 37˚C with a 5% carbon dioxide (CO 2 ) concentration, using a humidified incubator (23). The information of reagents that were used is presented in Table I.…”
Section: Methodsmentioning
confidence: 99%